EDMODO: IMPROVING STUDENTS’ WRITING SKILL - Wibowo, Siswo Edi (LPPM STKIP PGRI Bandar Lampung, 2019)
: Edmodo promotes students’ learning opportunities in the three following ways: creating a practical learning experience, allowing students to exchange positive feedbacks, and motivating students in the teaching-learning process. This research is a classroom action research that investigates the improvement of students’ writing skill taught by using Edmodo at STKIP PGRI Bandar Lampung. There are two cycles that the first cycle consisted of four sessions, and the second cycle consisted of three sessions. The population of this study was the second semester students in the academic year of 2018/2019. Both quantitative and qualitative data were employed to analyze the data. Writing test was conducted for obtaining quantitative data. On the other hand, qualitative data were in the form of an observation sheet, questionnaire sheet, and documentation. The treatments signified improvements of students’ writing skill in each cycle which is represented by the mean score. The mean score of pre-test was 56.76. It improved to 68.53 in the first cycle, and became 76.67 in the last cycle. The observation sheet, questionnaire sheets and documents proved that students performed active participation and engagement during the instructional process that fostered better skill in writing text.